PEMBELAJARAN MENULIS TEKS PROSEDUR DENGAN MENGGUNAKAN METODE CTL (CONTEXTUAL TEACHING AND LEARNING ) PADA SISWA KELAS X MAN CIMAHI - Dewi Widya Lestari; Herdiantina Dian; Rochmat Tri Sudrajat (IKIP Siliwangi, 2019)
Text Writing Learning Procedures using Contextual Teaching and Learning Method in Class X Student Cimahi. Writing is one of the aspects of language skills. In daily activities, we experience writing activities. Writing means the process of pouring ideas through writing, so the more we write, the more our thoughts are contained in them. The learning method was chosen in this research as the solution is by using CTL method. Contextual Teaching and Learning is a learning helps teachers connections between materials taught to real-world situations and encourages. Problems encountered in this research is how the implementation of learning and the results of writing the text of the procedure by using the Contextual Teaching and Learning method. The population amounted to 31 students. From the test results, there is an increase in the value of students before and after using the method of learning. From the initial test the average score of 52,15 students. While in the final test that has been using the method of learning, the average student score of 75,9. If the teacher uses the learning model using CTL method then the students can write the text of the procedure will increase.